Open Innovation in Tourism - Opportunities to Use Consumer’s Creative Potential in an Innovative Process - Hołderna-Mielcarek, Bernadeta (Studia Oeconomica Posnaniensia, 2018)
The paper presents the concept of open innovation, referring to the creative potential of tourist service consumers as a source of inspiration and cooperation between an enterprise and consumers in the innovation process. It presents theoretical-conceptual and empirical aspects of the discussed concept of innovation in the tourism sector. The analysis of the subject literature has allowed for the assumptions and methods supporting consumer involvement in particular stages of the innovation process to be indicated. The case studies exemplify obtaining the ideas of tourist service consumers as inspiration and cooperation in innovation development. The conclusions indicate the possibility of integrating the creative potential of consumers with other sources of knowledge in the innovation process, as well as the concentration of tourist involvement and their active participation primarily in the co-creation of tourism products and marketing communication. Further areas of research have been presented that could contribute to recognizing the impact of open innovations, which involve the potential of consumer tourists in the innovation process, on innovative abilities of businesses and tourist organizations, and activities that improve the effectiveness and efficiency of cooperation between tourism sector entities and tourists consumers in the innovation process.